Prominent Fatigue but No Motor Fatigability in Non-Hospitalized Patients With Post-COVID-Syndrome - Weich, Christian; Dettmers, Christian; Saile, Romina; Schleicher, Luise; Vieten, Manfred; Joebges, Michael (Frontiers in Neurology, 2022)
Objectives: Fatigue is a frequent and often disabling symptom in post-COVID patients. To better understand and evaluate the symptom of motor fatigue in the context of post-COVID syndrome, we conducted treadmill walking tests to detect the phenomenon of motor fatigability or to evaluate whether evidence of organic lesions of the motor system could be found, similarly to patients with Multiple Sclerosis. Method: Twenty-nine non-hospitalized post-COVID patients completed the Fatigue Scale for Motor and Cognitive Function (FSMC) questionnaire to determine the trait component of subjective fatigue before they were tested on a treadmill walking with a moderate speed up to 60 minutes or until exhaustion. During the walking test oxygen uptake, ventilation and acceleration data of both feet were collected. To determine motor performance fatigability, the Fatigue Index Kliniken Schmieder (FKS) was calculated using the attractor method. Results: The average walking duration was 42.7 ± 18.6 minutes with 15 subjects stopping the walking test prematurely. FSMC score revealed a severe cognitive (37.6 ± 8.2) and motor (37.1 ± 7.8) fatigue averaged over all subjects but only two subjects showed a FKS above the normal range (> 4) representing performance fatigability. There was no significant correlation between subjective fatigue (FSMC) and FKS as well as walking time. Absolute values of oxygen uptake and ventilation were in the normal range reported in in literature (r = 0.9, p < 0.05), although eight subjects did not produce a steady state behavior. Conclusion: Almost all patients with post-COVID syndrome and subjectively severe motor fatigue, did not show motor fatigability nor severe metabolic anomalies. This argues against an organic, permanent damage of the motor system, as it is often seen in MS. Many of the patients were - to our and their own surprise - motorically more exertable than expected.